PENGARUH KESEHATAN DAN TINGKAT KEMISKINAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TENGAH - Teguh Santosa; Anang Suryana (Institut Bisnis Muhammadiyah Bekasi, 2022)
This study aims to determine the Effect of Health and Poverty Rates on Economic Growth in Central Java Province. With Economic Growth as dependent or bound variables and Health and Poverty Rate as independent variables or free variables. This type of research is Quantitative. The secondary data used in this study is documentation obtained from the BPS (Central Statistics Agency) of Central Java Province. The sampling technique chosen is purposive sampling. The hypothesis was developed to see the influence of health and poverty rates on economic growth in Central Java. Hypothesis testing in this research is by using the method of Panel Data Regression Analysis and Multiple Regression Analysis. The results showed: 1) Health variables have a significant positive effect on economic growth in Central Java Province. 2) The variable poverty rate does not significantly affect economic growth. 3) Health variables and poverty rates simultaneously have a positive and significant effect on economic growth in Central Java Province.